Integration of Self-Regulated Learning with Show and Tell Technique in Improving Students' English Speaking Skills - Hamdani, Haris; Rafli, Zainal; Iskandar, Ifan (Universitas PGRI Adi Buana Surabaya, 2024)
This study investigates the effectiveness of Self-Regulated Learning and Show and Tell strategies to improve university students' English speaking skills. This study is a quantitative research using experimental design. The participants of this study were 30 students of Management study program as the experimental class and 30 students of Law study program as the control class at Bhayangkara University of Greater Jakarta. The results of this study indicate that learning models using Self-Regulated Learning and Show and Tell are more effective than using conventional learning models. Based on the results of interviews, students also stated that the integration of Self-Regulated Learning with Show and Tell is an effective combination of strategies in improving English speaking skills.